Studies in Neotropical Pseudophyllinae: A new genus of Cocconotini from the Colombian Andes and new subfamily assignment of the Dominican genus Anacaona (Tettigoniidae: Pseudophyllinae: Cocconotini) - Cadena-Castañeda, Oscar J.; Prieto-Cristancho, Daniel S.; Romero-Betancourt, Laura M.; Braun, Holger; García, Alexander García (Zootaxa, 2020)
Acuscercus eudaldoleondiazi n. gen et n. sp. from the Eastern slopes of the Colombian Andes is described, a typical long-winged member of the tribe Cocconotini, distinguished by peculiar morphology of male cerci. On the other hand, the Dominican genus Anacaona is moved from Cocconotini to the tribe Copiphorini (Conocephalinae). The status and tribal boundaries of Cocconotini and Eucocconotini are briefly discussed.